Export destinations and learning-by-exporting: Evidence from Belgium - Mauro Pisu (National Bank of Belgium, 2008)
This paper evaluates the causal effects of exports to different destination countries using a comprehensive dataset on Belgian manufacturing firms from 1998 to 2005. Initial evidence suggests that, before export market entry, exporters to more developed economies have superior productivity levels than non-exporters and firms exporting to less developed countries. Moreover, they seem to experience higher productivity growth rates in the post-entry period, suggesting learning-by-exporting effects. However, applying matching methodology to formally evaluate the causal effects of export market entry on productivity reveals no such impact. Thus, the productivity advantage of firms exporting to developed countries appears to be driven solely by self-selection.
Keywords: L1; D24; 330; Learning-by-exporting; export destinations; productivity; Außenhandelssektor; Export; Markteintritt; Lernprozess; Produktivität; Belgien